Design of Student Worksheet Based Pendidikan Matematika Realistik Indonesia (PMRI) to Improve Creative Thinking - Havilludin, Candra; Suparman, S (Universitas Muhammadiyah Surakarta, 2018)
Creative thinking is one of the skills that students must possess because this ability determines the success of students in achieving high learning achievement because students can better understand the lesson as a whole. However, the ability of the creative thinking of students in vocational schools in Gunungkidul Regency is still weak. This is demonstrated by the many students still have trouble resolving the question or problem which is not routine. The learning materials used by students and teachers is still limited, not using appropriate materials. The purpose of this research is to design of student worksheet based Pendidikan Matematika Realistik Indonesia (PMRI) to improve creative thinking of students. This research is preliminary research with a formative evaluation research methods. However, due to limitations of time, cost and energy, this study is limited to the stage of preliminary studies. This research was conducted in class X in SMK Muhammadiyah Tepus. The results showed that the student’s worksheet-based realistic mathematics education Indonesia to improve the ability of the creative thinking of the students was as follows; Student worksheet components consist of 1) title, 2) identity, 3) basic competencies, learning objectives), 4 and 5) the content of the student worksheet. The contents of a worksheetbased approach students PMRI: 1) presentation of the problem real or contectual, 2) understand the problem, 3) designing a mathematical model, 4) complete mathematical model, 5) discuss the answers and 6) concluded. An indicator of the ability of the creative thinking of students contained at this stage to understand the problem, designing a mathematical model, and complete mathematical model. Based on this initial research results, then it needs to be done further research to determine the feasibility and practicality of the design of learning materials in the form of worksheets students